2014
DOI: 10.21608/resoncol.2014.888
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evaluation focusing on prognostic impact of young age in Egyptian patients with colorectal Cancer, NEMROCK experience

Abstract: Worldwide, Colorectal cancer (CRC) is the most common malignant tumor of the gastrointestinal tract. It is the third most common cancer after lung and breast cancers and the second most common cause of death in both genders 1,2. CRC is a disease affecting mainly older persons, more than 90% of patients being diagnosed after the age of 55 years 3. However, epidemiologic features of CRC vary widely in different parts of the world 4. Epidemiological studies of CRC in Egypt showed that patients younger than 40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In our study, demographic data which comprises age and gender showed a signi cant difference regarding age where CRC group showed a higher mean of age with statistical signi cance when compared to both control and UC groups who showed a lower mean in their ages, this comes in accordance with other studies [3,23,24] which stated that colorectal cancer is mainly a disease of the elderly [23]or above the age of 55 [24,10]. These results were previously challenged in an Egyptian study [25] that recognized a relatively high percentage of patients diagnosed with CRC at a younger age group (between 20-40 years).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, demographic data which comprises age and gender showed a signi cant difference regarding age where CRC group showed a higher mean of age with statistical signi cance when compared to both control and UC groups who showed a lower mean in their ages, this comes in accordance with other studies [3,23,24] which stated that colorectal cancer is mainly a disease of the elderly [23]or above the age of 55 [24,10]. These results were previously challenged in an Egyptian study [25] that recognized a relatively high percentage of patients diagnosed with CRC at a younger age group (between 20-40 years).…”
Section: Discussionsupporting
confidence: 90%